(untitled) (Fiep Bulletin - online, 2024)
Introduction: Flexibility is understood as the ability of a joint to move within a maximum range of motion without causing injuries to the body. It is one of the components of physical fitness and is related to factors such as gender, age, and level of physical activity, among others. Having a satisfactory level of flexibility directly influences the improvement of an individual’s quality of life for everyday activities. Objective: To assess the level of flexibility, compared by gender, among students from a private school in the city of Campina Grande-PB. Methods: The field test was conducted on a sports court, evaluating 64 students, with 36 males and 28 females. The method used was the "Sit and Reach Test" (SRT), proposed by Wells and Dillon, using a Wells bench. Results: Female students achieved higher scores and better rankings on the Wells bench compared to male students. Conclusion: Female students demonstrated a better degree of joint flexibility in the hip and spine, as well as muscular extensibility of the hamstring muscles, compared to male students.